Variation in Epiphytic Lichen Biomass Occurring on Quercus semecarpifolia Smith, Saplings at Two High Altitude Forests of Central Himalaya, India - Arya, Vijay; Kumar, Balwant (Indian Forester, 2017)
Lichens have significant role in a forest ecosystem and are of considerable interest for forest management and climate studies. Altitude is an important factor which affects diversity, distribution and biomass of a species. The present study was carried out to assess the variation in epiphytic lichen biomass with increasing altitude. Authors have examined two high altitude forest sites of Uttarakhand, Central Himalaya for estimating quantitative biomass (dry mass) of epiphytic lichens occurring abundantly on Q. semecarpifolia (host). Both the forest sites were categorized into three altitudinal zones i.e. lower (2300-2400 m), middle (2400-2500 m) and upper (2500-2700 m). The macro lichens were harvested from different parts (bole, branch and twigs) of each selected sapling (n=54) across three altitudinal zones. The lichen biomass (g sapling-1) ranged from 64.0 ± 5 to 229.7 ± 4 and 159.7 ± 3 to 530.3 ± 4 at site A and B respectively. The number of lichen genera and biomass per sapling were strongly correlated with the altitude and the results showed that number of genera and biomass of lichens was increased with increasing altitude.